INDICATORS OF GENERAL AND SPECIAL PHYSICAL FITNESS OF WRESTLERS IN THE FORM OF " MILLIY KURASH " UNDER THE INFLUENCE OF INTENSIVE TRAINING EFFECTS - Kuvatov Elyor Khakmuradovich (Galaxy International Interdisciplinary Research Journal, 2021)
During the implementation of the developed experimental program, wrestlers were trained in the form of " Milliy kurash " using a significant amount of funds in the training process providing shock training effect. The effectiveness of the used intensive training methods was confirmed by a significant increase in the indicators of general and special physical fitness of kurash wrestlers.